Hubungan Konsumsi Ikan dengan Perkembangan Kognisi Anak Baduta (12-23 Bulan), Studi di Kecamatan Gandus Kota Palembang Tahun 2006 - Nurul S Nilawati; Sri A Nugraheni; Frieda NRH (Faculty of Psychology, Universitas Gadjah Mada, 2006)
Brain growth starts from prenatal period and ends at 2 years old. Fish contains protein, omega-3 and omega-6 Which are important for brain and cognitive development on children. The aim of this study was to investigate any correlation between fish consumption and cognitive development in children aged 12-23 months at Gandus sub district, Palembang. 106 children aged 12-23 months were selected using purposive sampling method in this cross-sectional study. Data on children and family characteristic were collected. Mother’s allocation time for their children were collected by interview using stucture questionnaires. Data on cognitive develop-ment were collected by testing subjects using Mental Development Index (MDI) of Bayley’s Scale for Infant Development (BSID) II. Dietary intake data were collected 2 days 24 hour food recall and Food Frequency Questionnaire (FFQ). There were no correlation between mother’s allocation time for their children, fish food consumption, and child cognitive development. There were negative correlation among daily energy, protein and energy, protein contribution from fish with cognitive development of children under two years respectively. Energy from fish contributedto 14,5% score of cognitive development of the children There were negative correlation between fish consumption and cognitive development of children under two years. Keywords: fish consumption, cognitive development, children under two years, Gandus sub District, Palembang.